Rainfall patterns and the contribution of litter in the caatinga dry tropical forest - Salgado, Eveline; Andrade, Eunice; Hevia, Joaquín; Nunes, Edson; Rodrigues, Meilla Marielle (Revista Ciência Agronômica, 2015)
The present study was designed to investigate the dynamics of rainfall patterns on the production and rate of decomposition of litter in the caatinga biome. To this end, a data series which had been recorded over 30 years (1981-2010) was used; the indicators taken into consideration being the irregular rainfall index, humidity index and consecutive wet and dry days. Litter was collected monthly over a period of two years (2009-2010) at 20 different locations, and totalled 480 samples. Samples were taken from all live individuals with a stem diameter of ≥0.03 m and a height of ≥1 m: 562 individuals in 25 recorded species were identified. The annual irregular rainfall index, calculated from the series, was 8.45, with a maximum precipitation of 1,763.9 mm (1985) and a minimum of 208.8 mm (1983). The difference in annual rainfall during 2009/2010 was 787.9 mm, 2010 showing greater temporal variability when compared to 2009. Using the humidity index, these years were classified as very wet and very dry respectively.  The total annual rainfall influenced the annual production of litter, with 6034.22 kg ha-1 and 3311.96 kg ha-1 for 2009 and 2010 respectively. The temporal distribution of rainfall brings forward leaf senescence. In 2010 eight dry spells were recorded, and those that occurred in May and June particularly caused the leaves to fall earlier by almost 60 days, demonstrating that the distribution of rainfall over time speeds up the aging of leaves.